Análise da convecção forçada no escoamento bidimensional laminar em dutos circulares em variáveis primitivas via GITT. - Lopes, Mabel de Morais (2012)
In this study the forced convection in the laminar flow in simultaneous developing is studied by applying the Generalized Integral Transform Technique to provide a hybrid analytical solution for the fields of velocity, pressure and temperature in circular ducts. The Continuity, Navier-Stokes, Poisson and Energy equations are formulated using primitive variables,knowing that the Poisson Equation was obtained from some mathematical manipulation made on the Navier-Stokes equations. The integral transformation is done in the Momentum equation in x, Poisson and energy equations, and the resulting equations are solved using the IMSL, DBVPFD subroutines and recovering the original potential for each profile studied. In this way it is possible to find a solution to the system by means of an expansion in terms of convenient eigenfunctions, to circular ducts, the eigenfunctions will be Bessel functions. In the following, some results from a practical point of view will be calculated and exhibited graphically such as: The Nusselt number, the f Re value, the study of the convergence profile of the velocity field, the mean velocity, the temperature, the mean temperature, pressure and the mean pressure in the middle of the duct will be analyzed. The results will be compared with the ones found in the literature to validate and adjust the model.